Test protocol and rheological model influence on determining the rheological properties of cement pastes - Campos, R. S. [UNESP] (2021)
The rheological characterization of cement pastes, mortars and concretes considers the rheological parameters of complex suspensions, composed by different materials, which interact both chemically, and physically. In addition, distinct test conditions and diverse mixture compositions may also interfere on determining the composites’ rheological properties. Along these lines, this work evaluates the test protocol and the rheological model influence on the rheological characterization of cement pastes. To do so, we established four different test protocols, with two maximum shear rates (50 and 100 s−1) and two distinct shearing methods (single-staged and multiple-staged). Bigham, modified Bingham and Herschel-Bulkley models were used to fit the experimental data. The water/cement mass ratio of the studied pastes ranged between 0.40 and 0.65. Our analysis indicates that the test protocol and the rheological model exerts significant influence on determining rheological parameters. In general, Herschel-Bulkley model showed better fitting to experimental data. More reproductive results were verified on the multiple-staged shearing with a maximum shear rate of 100 s−1.